Diagnóstico de salud bucodental y factores de riesgo en el colegio Nacional Mixto Vilcabamba y Jardín Antonio Peña Celi de la parroquia Vilcabamba año 2013 - Cuenca Ordoñez, Adriana de los Ángeles (2013)
Dental caries and periodontal disease worldwide are most prevalent diseases. Currently its distribution and severity vary according to many factors, including environmental, cultural partner, economic, etc. Health services especially dental care, suffer inequities in coverage , which mainly affects rural areas, this combined with the high poverty rates, determined that in these areas there is a higher prevalence of oral disease .It is necessary to acknowledge that there is a lack of information about the oral health status of the most distant of our county, which is why it has seen fit to make this research work to expand knowledge based on the degree of health and illness of the population of the parish Vilcabamba. To carry out research had the following objectives: to make a diagnosis of oral health of students “National Joint College Vilcabamba " and Garden " Antonio Peña Celi " Vilcabamba the parish , by identifying risk factors influence oral health , and the determination of the prevalence of major diseases. The quantitative study was a prospective, descriptive , the universe was made up 763 students from the two institutions. The sample was sample of 171 students, of which 159 are members of the second and third years of high school National Joint College Vilcabamba, and 14 students are belonging to the Garden “Antonio Peña Celi . To carry out the work was done filling history and survey, evaluating brushing technique and the data we were able to show that dental caries and gingival inflammation are the most prevalent diseases in the sample, the same as are influenced by improper brushing technique, the low frequency of brushing and visiting the dentist low . As results were obtained: 72 % of dental caries, gingival inflammation 14.6% , 24 % of dental fluorosis and 79.9% of malolusiones . After completing the study it can be concluded that there is a high rate of tooth disorder , which adversely affect the general health of the population , affecting the proper development of the individual and of the community as a whole. As recommended promotion and prevention campaigns oral. Based on the above we can say that the procedures carried out at both institutions allowed me to inform students regarding measures to promote oral health , oral hygiene , eating habits, trying to expand knowledge and encourage students awareness thoughts , students , teachers, and parents to benefit oral health welfare of students .